Improving interfacial strength of epoxy composites by constructing "palm‐tree"‐like structure on carbon fiber. Issue 9 (15th June 2021) - Lu, Zhaohui; Li, Muxuan; Liang, Mei; Chen, Yang; Zou, Huawei; Ren, Xiancheng
Abstract: Modified graphene oxide (GO)/carbon fiber (CF)/epoxy (EP) composites are prepared by combining grafting and sizing methods. The effects of different molecular chain lengths of poly(oxypropylene)amines on the surface grafting of GO, as well as the interfacial structure and properties of CF and EP resin after sizing, were investigated. The "palm‐tree"‐like structure interfacial enhancement theory was innovatively proposed. The characterization results showed that the short‐chain poly(oxypropylene)amines modified GO (D400‐GO) had a good effect on the interfacial properties of CF and EP resin. When the content of D400‐GO was 0.20 wt%, the interfacial shear strength was as high as 70.56 MPa, which was 37% higher than the virgin CF. In this article, a new theoretical model is proposed for multiscale interfacial enhancement. Abstract :